Numerical Names as Nominative Base of the Tatar Language System - Zagidulina, Albina; Salakhova, Ruzilya; Sibgaeva, Firuza; Huseynova, Mahira (Journal of History Culture and Art Research, 2018)
The problems of word formation intensively studied during all periods of the development of linguistics have not lost their relevance at the present time, since word formation is the most important means of replenishing the vocabulary of the language. The vocabulary of the language is in a state of almost continuous development, reflecting the changes that happen in all areas of people’s lives and activities. The continuous process of creating new words in a language is a complex cognitive process that takes place under the influence of extralinguistic factors, nevertheless it follows the existing prototypes used by analogy in accordance with structural models. Speaking of the word formation model, we mean a certain set structure that has a generalized categorical meaning and develops a number of other hierarchically related lexical meanings, implying not only a structure, but also certain semantics. The word-formation model is at the beginning of the word-forming process, determining how the initial elements of the language build a new name. Of particular interest for research in this regard are the derived words that are formed from the stems with semantics of quantity. As is known, the names of numerals are not formed from other parts of speech, but they themselves freely participate in the word-formation of nouns, adjectives, adverbs, verbs and other parts of speech. In Tatar linguistics there are practically no special studies concerning the numerals as a nominative base of the Tatar language system. The need to study the names of numerals as an independent motivational unit of language determines the relevance of this work. The results of the research can be used to work out lecture courses in general linguistics, lexicology, morphology, word formation of the Tatar language.